Caulfield, Cauliflower, and other vegetables : (A possible dialectics on The Politics of Misunderstanding). - Miessen, Markus; de Schipper, Jessica (Utrecht : Utrecht Graduate School of Visual Art and Design, 2016)
Schreiber, Constanze ; Zapata Zuluaga, Felipe ; Choi, Goeun ; Soriano, Iliana ; Holowko, Kathy ; Országhová, Kristina ; KT Rangnick ; Angelovska, Marija ; Hassanain, Ola ; Hukku, Pooja ; Gregoriou, Stavroula ; Holtrop, Willem
Published on the occasion of MaHKU MA Fine Art Graduation Show 2016
boek